2018
DOI: 10.1126/science.aat8196
|View full text |Cite
|
Sign up to set email alerts
|

Quantum metasurface for multiphoton interference and state reconstruction

Abstract: Metasurfaces based on resonant nanophotonic structures have enabled innovative types of flat-optics devices that often outperform the capabilities of bulk components, yet these advances remain largely unexplored for quantum applications. We show that nonclassical multiphoton interferences can be achieved at the subwavelength scale in all-dielectric metasurfaces. We simultaneously image multiple projections of quantum states with a single metasurface, enabling a robust reconstruction of amplitude, phase, cohere… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
197
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 281 publications
(197 citation statements)
references
References 39 publications
0
197
0
Order By: Relevance
“…where { 3 | = {1, … ,9}} are real numbers. Equation (7) satisfies the condition defined by Eq. (3) and has the DOF of 9.…”
Section: Designing Non-paraxial Diffractive Optical Elements (Does)mentioning
confidence: 99%
See 2 more Smart Citations
“…where { 3 | = {1, … ,9}} are real numbers. Equation (7) satisfies the condition defined by Eq. (3) and has the DOF of 9.…”
Section: Designing Non-paraxial Diffractive Optical Elements (Does)mentioning
confidence: 99%
“…By engineering the building blocks of the photonics materials and devices, the behavior of light, such as phase, amplitude and polarization of transmitted light and near field responses of wave, can be accurately controlled. Diverse photonic devices ranging from diffractive optical elements (DOE) to metamaterials (MM) and metasurfaces (MS) 1,2 , are designed for the extensive applications such as virtual/augmented reality display 3,4 , miniaturized imaging systems 5,6 , and quantum optics platform 7 . However, the complex mechanism of light-matter interaction prevents an intuitive strategy for the design of the building blocks in the photonic devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the capability of direct engineering the optical response in both the near‐field and far‐field domain, metasurfaces has attracted great attention in manipulating the quantum state of light, [ 118 ] replacing the current bulky optical elements for the quantum measurements, such as lenses, beam splitters which has been commonly used in the quantum interference experimental measurements. In a recent work by Wang et al., [ 119 ] the researcher used the metasurface to realize and enable the single‐ and multiphoton state measurements based on the interaction of light with the subwavelength thin nanoresonators, as depicted in Figure a. It has been shown that using the silicon metasurface, it is able to reconstruct the multiphoton density matrices.…”
Section: Quantum Metasurface and Photon Sourcementioning
confidence: 99%
“…Integrated robust broadband tunable Bell-state generators are of great potential for a wide range of applications in quantum photonics. Having access to a high quality photon-pair source will allow experimental tests of novel concepts, such as devices designed for quantum tomography [41,42], quantum state manipulation and storage [43], quantum state in-line reconstruction [44], quantum mechanics tests [45] and many others [46]. Tunability makes this source extremely versatile, while broadband operation gives the option to select the right output wavelengths for the task.…”
Section: Potential Applications In Quantum Photonicsmentioning
confidence: 99%